Om sambandet mellan folkmusikinsamling och tonsättning av folkmusikbaserade verk: – med utgångspunkt i samarbetet mellan Karl Tirén och Wilhelm Peterson-Berger - Ternhag, Gunnar (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2000)
The connections between the collection of folk music and the creating of compositions based on folk music – as seen in the light of the co-operation between Karl Tirén and Wilhelm Peterson-Berger. Two important elements in the musical life of Sweden at the turn of the century 1900 were the collecting of folk music and the creating of folk music-based compositions. Which were the connections between these efforts? This question is central in this article, which is divided into two parts. The first half describes the co-operation between Karl Tirén (1869-1955) and Wilhelm Peterson-Berger (1867-1942). Karl Tirén (1869-1955) collected yoiks among saamis (lapps) in Sweden in the years 1909-1916 and published a great deal of his material in 1942: Die lappische Volksmusik. To his profession Tirén was a stationmaster, working in several places in the north of Sweden. Wilhelm Peterson-Berger was one of the most influential composer of his time in Sweden, not only because of his musical works, but also for his position as a leading reviewer. Tirén and Peterson-Berger were close friends for a longer period. They encouraged each other – within folk music only during a limited time. Their involvement in folk music is manifested in Peterson-Berger’s third symphony, Same ätnam (1913-15): five of its themes originate from Tirén’s collection of yoiks. The second half contains a discussion about the relation between the two activities: In principal, there are four different ways for impulses (and music material) from folk music collectors to reach composers: Firstly, the collector and the composer have a close collaboration – like in the case described above. They nearly have the same kind of involvement in folk music, which results in compositions that focuses the folk music itself. The second way is at hand, when the composer gets his/her music material from an already existing collection of folk music. The collector is then absent (from the composer’s point of view). The chosen music material is often handled as “absolute music”. Thirdly, the collector and the composer can be one and the same person. The composition-process then starts with the recording of a certain folk tune. The fourth way is the most hidden, but on the other has the strongest impact upon the musical works. The composer in question does not use authentic folk music, but knows it so well after studying collected melodies that he/she him/herself can write music in a “reliable” folk music-style.